2010
DOI: 10.1007/s12369-010-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Expressing Emotions with the Social Robot Probo

Abstract: Probo is a huggable animal-like robot, designed to act as a social interface. It will be used as a platform to study human robot interaction (HRI) while employing human-like social cues and communication modalities. The robot has a fully actuated head, with 20 degrees of freedom, capable of showing facial expressions and making eyecontact. The basic facial expressions are represented as a vector in the 2-dimensional emotion space based on Russel's circomplex model of affect (Posner et al. in Dev. Psychopathol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 22 publications
2
101
0
3
Order By: Relevance
“…showed that people are able to recognize the emotional expressions of Kismet (Breazeal, 2002) and Probo (Saldien et al 2010). Such evaluations are useful, and show that it is possible to develop robots that can form recognizable emotional expressions.…”
Section: Emotion and Contextmentioning
confidence: 93%
See 4 more Smart Citations
“…showed that people are able to recognize the emotional expressions of Kismet (Breazeal, 2002) and Probo (Saldien et al 2010). Such evaluations are useful, and show that it is possible to develop robots that can form recognizable emotional expressions.…”
Section: Emotion and Contextmentioning
confidence: 93%
“…For instance, the FACS was widely adapted to create at least six basic and discrete facial expressions (joy, sadness, anger, fear, disgust and surprise) for some non humanoid robotssuch as Feelix (Canamero and Fredslund, 2000), Kismet (Breazeal, 2002), Aryan (Mobahi et al 2003), EDDIE (Sosnowski et al 2006), and Probo (Saldien et al 2010). The FACS was initially developed as a set of guidelines for recognizing the facial expressions of humans but has been found to be a reliable tool for creating believable versions of these basic facial expressions (e.g., overall recognition rate of the basic facial expressions for Probo was 84%, followed by Kismet with 73%, while Eddie achieved a bit lower rate with 57%.…”
Section: Creating Recognizable Facial Expressions For Social Robotsmentioning
confidence: 99%
See 3 more Smart Citations